Organization and development of document flow on children’s literature in Azerbaijan (Second half of the 19th century and the beginning of the 20th century) - Nadir, İsmayilov and Shahla, Ganbarova (Technium Social Sciences Journal, 2022)
It allows you to track and analyze the pace of formation and development of any sectoral document flow in different periods, to reflect on the requirements and realities of that period, as well as the level of development of science and culture. Following the process of formation and development of the flow of documents on children’s literature in Azerbaijan, the historical development processes and stages of a large number of existing documents revive the panorama of the period in terms of both socio-political and material-spiritual values. The article examines the formation and development of the flow of documents on children’s literature in Azerbaijan in the second half of the XIX century and the beginning of the XX century, the factors influencing this process.